A Study on Employee Well- Being and HRM Practices at the Selected Private Hospitals in Uttar Pradesh - Swati Tyagi,; Dr. Nisha Agarwal, (The Bioscan, 2025)
The majority of organizations want to be in good condition. Thus, it stands to reason that if their staff members are in good health and are fit and well, this must undoubtedly help the business operate smoothly. For a business to continue operating profitably and efficiently, its workforce is crucial. The importance of workplace health and employee wellness policies to businesses is growing, as more companies realize the benefits to their operations and the potential impact they might have. The welfare of the workforce is vital to the operation and survival of businesses because HR policies improve the value of human capital with the help of flexibility and development.